ADAPTASI SOSIAL GAY MUSLIM INDONESIA TERHADAP AGAMA DAN KELUARGA THE SOCIAL ADAPTATION OF GAY MUSLIM TO RELIGION AND FAMILY - Adihartono, Wisnu (P2KK LIPI, 2020)
The LGBT groups in Indonesia have little or no power and limited access to fight for their rights. Growing up in a system where one cannot be or say who they truly are, places them in a position where they are in a constant state of having to negotiate life within a hostile environment. This paper will look their (social) adaptation between their religion (Islam) and their family. They have to obey their religion, as well as they also have to obey and respect to their family in order to preserve the family?s honor. Those complexities raise a hierarchy, which is side by side with the religious teachings, culture and norms that causes a difficulty for them to come out showing as a gay. For this paper, I took the data from my doctoral research at Ecole des Hautes Etudes en Sciences Sociales (EHESS), France which I completed in 2015. For the purposes of this paper, I only used ten questions that are very closely related to religious and family issues. Kelompok Lesbian, Gay, Biseksual, dan Transjender (LGBT) di Indonesia memiliki akses yang sangat terbatas untuk memperjuangkan hak-hak mereka. Tumbuh dalam sistem di mana seseorang tidak dapat mengatakan siapa mereka sebenarnya, menempatkan mereka dalam posisi di mana mereka berada dalam keadaan konstan. Mereka harus melakukan adaptasi dalam lingkungan yang bermusuhan. Makalah ini akan melihat adaptasi (sosial) mereka di antara agama (Islam) dan keluarga. Mereka harus mematuhi agama mereka dan juga harus menghormati keluarga mereka untuk menjaga kehormatan keluarga. Kompleksitas itu memunculkan hierarki dalam ajaran agama, budaya, dan norma-norma yang menyebabkan mereka sulit tampil sebagai gay. Untuk makalah ini, saya mengambil data dari penelitian doktoral saya di Ecole des Hautes Etudes en Sciences Sociales (EHESS), Perancis yang saya selesaikan pada tahun 2015. Untuk keperluan makalah ini, saya hanya menggunakan sepuluh pertanyaan yang sangat erat kaitannya dengan agama dan masalah keluarga.